Studi Keanekaragaman Mikroorganisme Di Ekosistem Air Tawar - Rahmawati, Naila; Wulandari, Suci (Journal of Science and Mathematics Education, 2025)
Freshwater ecosystems serve as habitats for various microorganisms that play a crucial role in ecological balance and biogeochemical cycles. This study aims to analyze the diversity of microorganisms in freshwater ecosystems using conventional microbiological approaches and DNA-based analysis. Samples were collected from several distinct freshwater bodies, including rivers, lakes, and swamps, to identify variations in microbial communities.The results show that the microorganisms found belong to various groups, including bacteria, archaea, and fungi, with dominant genera such as Pseudomonas, Bacillus, and Aspergillus. Environmental factors such as pH, temperature, nutrient content, and dissolved oxygen levels significantly influence the composition of microbial communities. Metagenomic analysis revealed the potential of microorganisms in bioremediation processes, such as the degradation of organic pollutants and nitrogen fixation. Additionally, microorganisms with probiotic potential were identified, which could be utilized in the aquaculture industry and environmental health. In conclusion, freshwater ecosystems harbor a high diversity of microorganisms with various ecological functions and potential applications in environmental and biotechnological fields. Further studies are needed to explore the specific roles of microorganisms in freshwater ecosystems and their potential in the development of environmentally friendly technologies